Generation of recombinant scFv antibody against Ochratoxin A (OTA) - Ranya Pranomphon; Witsanu Srila; Montarop Yamabhai (Indonesian Journal of Biotechnology, 2017)
Ochratoxin A (OTA) is a mycotoxin commonly found in agricultural products and can accumulate in the blood and tissues after that consuming contaminated food. Recombinant single-chain antibody fragments (scFv) against OTA were selected from phage display libraries. After of one round of biopanning against BSA-conjugated OTA (OTA-BSA), 52 and 6 phage clones displaying scFv antibodies were isolated from human (Yamo I.3) and rabbit (Bozmix I.2) libraries. Two phage clones (one from each libraries, i.e., yOTA1e3 and bOTA2a9) showed binding to free toxin by competitive ELISA. The soluble scFv antibodies were produced by superinfecting phage clones into E. coli suppressor strain HB2151. The scFv genes from these two phage clones were sub-cloned into pKP300ΔIII vectors to generate scFv-AP fusions. The binding affinity (IC50) of antibody derived from human library was higher than those from rabbit library. The binding property of recombinant antibody in the form of scFv-AP was better than those of soluble scFv form. Cross-reactivity analysis indicated that the two recombinant antibodies did not cross-react with other soluble toxins, namely AFB1, DON, ZEN and FB. The ability to use the recombinant scFv-AP to detect contaminated toxins in agricultural product (corn) was demonstrated.